An exploration of teaching reform of management course based on rain class and participatory teaching under OBE concept - Xie, Pingping; Huo, Bin (Edelweiss Applied Science and Technology, 2024)
Management is the core course of business administration majors. In order to drive educational modernization through educational informatization, this article explores the teaching reform of management based on the concept of learning output education (OBE). It is guided by student output and follows the principle of "reverse design and positive implementation". In terms of implementation, it is specifically divided into learning goal reconstruction, course content integration The teaching process and the construction of an evaluation system are four steps. During the teaching process, the implementation of rain classroom and participatory teaching mode has broken through traditional time and space limitations, extending the interaction and communication between teachers and students from the classroom to pre class and post class, achieving a good loop of "pre class in class after class". This teaching reform practice can promote the improvement of the quality of management teaching and is conducive to cultivating high-quality management talents.